Family Welfare of Women Traders in Kebon Roek Market, Ampenan Subdistrict, from the Maqasid Syariah Perspective - Hayyul Ihsan; Akhmad Jufri; Moh. Huzaini (Tinta Emas Institute, 2023)
The aim of this research is to determine the welfare of the families of women traders in the Kebon Roek market, Ampenan sub-district, from a Maqasid Syariah perspective. This research uses a qualitative approach with descriptive methods. The data collection techniques used were observation, interviews and documentation. Determining informants in this study used purposive and snowball. The data validity method used is the triangulation method. Data analysis methods use data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the research that has been carried out, it can be seen that the welfare perspective of Maqasid Syariah, namely in maintaining religion (Hifz al-Din), has been implemented, but the women traders do not immediately pray when there are buyers. Protecting the soul (Hifdz al-Nafs), has been achieved by consuming halal and good food and having a suitable place to live, Maintaining the mind (Hifdz al-Aql'), has been achieved by strengthening understanding by listening to lectures on television and attending recitations, Maintaining offspring (Hifdz al-Nasl), has been implemented by providing education to their children in the form of general and religious education and safeguarding assets (Hifdz al-Mall) has been implemented by them managing their assets in a halal way, using it for tithes, charity and meeting their needs and sending their children to school.